Insular Epilepsy: Clinical, Electrophysiological Features, and Surgical Treatment - Marashly, Ahmad; Lew, Sean; Inglese, Christopher; Mueller, Wade (Journal of Pediatric Epilepsy, 2017)
The insula, also known as the fifth lobe of the brain, is a phylogenetically older part of the cortex that forms the floor of the Sylvian fissure. It is densely connected with multiple regions in the brain, reflecting its rich functionality. Epilepsy arising from the insula has been only relatively recently described and characterized in details. Besides having unique features, the insula is believed to be the origin of seizures resembling those of suspected temporal or frontal lobe epilepsy that do not respond to traditional surgical resections. In this review article, we describe the gross and functional anatomy of the insula, clinical and electrophysiological manifestations of insular epilepsy, and surgical evaluation and treatment approaches.
Keywords: epilepsy; insula; semiology; surgery